2023
DOI: 10.3390/app13179890
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition for Photo and Video Surveillance Based on Machine Learning and Visual Analytics

Oleg Kalyta,
Olexander Barmak,
Pavlo Radiuk
et al.

Abstract: Modern video surveillance systems mainly rely on human operators to monitor and interpret the behavior of individuals in real time, which may lead to severe delays in responding to an emergency. Therefore, there is a need for continued research into the designing of interpretable and more transparent emotion recognition models that can effectively detect emotions in safety video surveillance systems. This study proposes a novel technique incorporating a straightforward model for detecting sudden changes in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In some VA tasks, particularly when applying the principle of HITL, there arises a need to determine the coefficients of the hyperplane from points that belong to or (more often) are near this hyperplane [29]. The determination of the hyperplane coefficients is proposed in a manner analogous to work [30].…”
Section: Basic Definitions and Conceptsmentioning
confidence: 99%
“…In some VA tasks, particularly when applying the principle of HITL, there arises a need to determine the coefficients of the hyperplane from points that belong to or (more often) are near this hyperplane [29]. The determination of the hyperplane coefficients is proposed in a manner analogous to work [30].…”
Section: Basic Definitions and Conceptsmentioning
confidence: 99%
“…Similarly, the use of facial expressions for ERS towards video surveillance was proposed in [38]. It has been highlighted that video surveillance systems nowadays are operated via human capabilities to interpret behavior through video surveillance, which leads to delays in responding to emergencies [38].…”
Section: Ers Applicationsmentioning
confidence: 99%
“…Similarly, the use of facial expressions for ERS towards video surveillance was proposed in [38]. It has been highlighted that video surveillance systems nowadays are operated via human capabilities to interpret behavior through video surveillance, which leads to delays in responding to emergencies [38]. The experiments concluded that the implementation of facial recognition as part of ERS towards video surveillance system can improve the reliability of abnormal behavior detection via facial expressions depending on different emotions and environmental conditions.…”
Section: Ers Applicationsmentioning
confidence: 99%
“…Research in this area, especially studies investigating surveillance video anomaly detection (SVAD) using deep learning [9], is progressing rapidly. This research domain has evolved to encompass a broader scope, extending beyond behavior-based detection to include advanced areas like human facial emotion recognition for anomaly detection [10], illustrating the expanding reach and depth of investigations in this field. These systems function by capturing real-time images across various indoor and outdoor settings, both public and private.…”
Section: Introductionmentioning
confidence: 99%